The first Pharaohs their lives and afterlives - Dodson, Aidan 1962- (The American University in Cairo Press, 2021)
Introduction -- The First Dynasty -- The Second Dynasty -- The Third Dynasty -- Limbo -- Resurrection -- Appendices. Chronology; Royal names; Dimensions of royal tombs; The First Three Dynasties according to the surviving extracts from Manetho
Includes bibliographical references and index
Keywords: Geschichte 3100-2575 B.C; Archäologie; Pharao; Grab; Ägypten -- Altertum; Tombs / Egypt; Egypt / Kings and rulers; Egypt / History / Early Dynastic Period, ca. 3100-ca. 2686 B.C; Egypt / History / Third dynasty, ca. 2649-2575 B.C; Egypt / Antiquities; Biografie